Single particle analysis of soil dust by aerosol time-of-flight laser mass spectrometry - Guo, Xiao-Yong; Zhao, Wen-Wu; Huang, Ming-Qiang; Zheng, Hai-Yang; Fang, Li; Zhang, Wei-Jun (Oficyna Wydawnicza Politechniki Wrocławskiej, 2007)
A laboratory study was carried out to investigate the single particle soil dust using aerosol time-of-flight mass spectrometry. The presence of crustal elements is observed in the mass spectra of individual particles. Potassium and iron constitute the two most commonly detected cations. Other common cations observed in the mass spectra of soil particles include sodium and magnesium. According to a large number of single aerosol diameters, we obtained the size distribution. Peaks in the positive ion mass spectra enable us to identify individual dust particles in atmospheric samples and track chemically distinct dust particles in the atmosphere using aerosol time-of-flight mass spectrometry.
Optica Applicata, Vol. 37, 2007, nr 3, s. 229-235
Keywords: optyka; mass spectrometry; aerosols; trace elements; particulate matter